Education Dunedin (New Zealand : Economic Development Unit [production company])
Dunedin is the principal city of the province of Otago, situated in the South Island of New Zealand, in the southern corner of the Asia Pacific rim. Dunedin has four outstanding tertiary institution, all situated in one unique campus setting. they are the University of Otago, the Dunedin College of Education, Otago Polytechnic and the Otago Language Centre
Keywords: Organizational learning